Justification of a set of measures for forming an institutional environment and a management system for defense industry complex diversification - D. Yu. Baydarov; D. Yu. Faikov (Управление)
The wave-like nature of the state defense order confirms the need to diversify the defense enterprises’ activities as a way to improve their sustainability and development, which allows them to maintain the required level of the country’s defense capability and economy mobilization readiness. Diversification into the civilian goods sphere makes it possible to use the defense industry complex competencies and resources to strengthen the country’s technological sovereignty and move towards technological leadership.   The purpose of the study is to substantiate a set of measures for forming institutional environment and management system of defense-industrial complex diversification.   The article considers the foreign experience of defense industry diversification and identifies the principles of interest for Russian enterprises. The systemic difficulties of defense industry complex diversification of methodological, institutional, organizational, socio-economic nature have been revealed. The fundamental bases for its effective implementation have been substantiated, including institutional conditions formation with a special administrative and legal regime, strategic technology transfer system organization, scientific and technological forecasting and planning system, the creation of a defense-industrial complex diversification three-level management system and a legal framework. The basis for the latter should be the federal law “On Diversification of the Defense Industrial Complex Organizations’ Activities”, and the first step should be the preparation of the Defense Industrial Complex Organizations’ Activities Diversification Concept.